Emerging Issues in Financial Development : Lessons from Latin America - Didier, Tatiana; Schmukler, Sergio L. (Washington, DC: World Bank, 2013)
Since the 1990s, the financial systems in developing and developed countries have gained in soundness, depth, and diversity, prompted in part by a series of financial sector and macroeconomic reforms aimed at fostering a market-driven economy in which finance plays a central role. Latin America has been one of the regions at the forefront of these changes and offers a good laboratory of where the challenges in financial development lie. Despite all the gains in financial development, there is still a nagging contrast between the intensity of financial sector reforms implemented over the past 20 years in many countries and the actual size and depth of their financial systems. In the case of Latin America, in many respects it remains underdeveloped by international comparisons.